Fish capture volume of frigatetuna (Auxis thazard) as a one of fisheries commodity in Singkawang City - Alfian Johansyah; Lufti Anggadhania (Journal of Fisheries and Marine Applied Science, 2023)
Frigate tuna is one of the main commodities in the fisheries capture sector in Singkawang City. Fish capture was conducted throughout the year. Therefore, this study aimed to observe the volume of frigate tuna catches and their production value during the 2018 – 2020 period for annual and monthly periods. The data used in this study were catch volume and the production value of frigate tuna. Based on these observations, the total catch volumes in 2018, 2019, and 2020 were 237,885 kg, 240,013 kg, and in 2020 it and 265,026 kg, respectively. For the total volume of frigate tuna catches for the monthly period, the highest value was recorded in November, which was 95,465 kg. The lowest capture volume was observed in August, at 27,043 kg. Its production value during 2018 – 2020 is IDR 4,971,889,000 (2018), IDR 4,924,906,000 (2019), and IDR 5,099,693,000 (2020). Meanwhile, the monthly production value during 2018 – 2020 was in March of IDR 2,027,302,000 and the lowest was in August IDR 531,027,000.